The JCT 05 standard building sub-contract - Barnes, Peter (Oxford ; Malden, MA : Blackwell Pub., 2006)
Whilst there are a number of books on the main forms of building contract, very few deal with subcontracting. This book examines the new JCT Standard Building Sub-contracts for use with the radically revised 2005 JCT Standard Building Contract. It looks at the key contract conditions, considers the rights and obligations of the parties and how risk is allocated, and discusses the main practical problems that arise.
Table of Statutes and RegulationsClause, Recitals, Articles and Sub-Contract Particulars Index; Subject Index.
Includes indexes.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Construction contracts -- England; Construction industry -- Subcontracting -- England; Construction -- Industrie -- Sous-traitance -- Angleterre; LAW -- Military; Construction contracts; Construction industry -- Subcontracting; England